AL-QUR’AN DALAM TRADISI MANGANAN DI DESA SOKO MEDALEM KECAMATAN SENORI KABUPATEN TUBAN - Ummi Muizzah (STAI AL-ANWAR SARANG, 2019)
This study examines the reception of the Qur'an in the people of Soko Medalem, Senori, Tuban in their daily life, especially in the Manganan ritual which is part of the traditions of the ancestral heritage of the local community. By using the living Qur'an approach, the focus of this study is the depiction of the form of Soko Medalem community's reception of Al-Qur'an which is transformed into their daily life and a tradition that has been deeply rooted as their cultural basis. To answer this research problem, the author uses the theory of sacred symbols and the cultural interpretation of Clifford Geertz which explains a cultural system as a sacred symbol which then influences the social relations of society it self. The result of this study reveals that the Qur'an is perceived as part of the culture and life of the people of Soko Medalem. Al-Qur'an is considered as part of cultural rites, so its sacredness ledit to be part of culture which is also full of sacred meanings. The practice of al-Qur'an in the Manganan ritual is khataman al-Qur'an which is the core of the tradition. There is a special motive for the people of SokoMedalem that is they believe in Al-Qur'an rite to bring prosperity and blessings.